(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2019)
Abstract: The article began from the need of making sense on analyzing the current formation educational policies and teaching careers. The research was performed from a careful comparative between World Bank´s documents and the related literature, using the magazines "Nova Escola" ("New School") and "Gestão Escolar" ("school administration") in the period of 2008-2017. In order to understand such policies, together with the press media artefacts, a theoretical combination between the historical-critical theory and the post-critical theory elements was articulated. This article systematizes the theoretical references tension and rapprochement points, with the purpose of sustaining the options and the educational policies analysis regarding convergences that come from the influence arena. The study highlights, at this historical moment, the consequences for the research in general educational policies and for formation policies and teaching careers in particular. Keywords: Educational Policies. Historical-Critical Theory. Post-Critical Theory. Combined Theorizing.